Urinary metabolites of polycyclic aromatic hydrocarbons in Saudi Arabian schoolchildren in relation to sources of exposure - Alghamdi, Mansour A.; Alam, Mohammed S.; Stark, Christopher; Mohammed, Nuredin; Harrison, Roy M.; Shamy, Magdy; Khoder, Mamdouh I.; Shabbaj, Ibrahim I.; Göen, Thomas (Environmental Research, 2015)
Polycyclic aromatic hydrocarbons contain a number of known carcinogenic compounds, and urinary biomarkers have been widely used as a measure of exposure but quantitative relationships with exposure variables have proved elusive. This study aimed to quantify the relationship between exposures to phenanthrene and pyrene from atmospheric and dietary sources with the excretion of 1-hydroxypyrene and hydroxyphenanthrenes in urine as biomarkers of exposure. The study population consisted of 204 male schoolchildren attending three schools in different parts of Jeddah, Saudi Arabia who provided urine samples on each of three consecutive days. Outdoor air measurements of polycyclic aromatic hydrocarbons were made at the schools and the children provided information on diet, exposure to environmental tobacco smoke and incense, and various lifestyle factors through a questionnaire. Mixed models with random effects for subjects nested within site were fitted in order to examine the relationship between exposure variables and urinary PAH metabolites. A unit increase (1 ng m(-3)) in ambient pyrene (particulate plus gaseous phase) was associated with a 3.5% (95% CI: 1.01%, 5.13%) increase in urinary 1-hydroxypyrene concentration. A unit increase in ambient phenanthrene was associated with a 1.01% (95% CI: 0.03%, 2.02%) increase in total hydroxyphenanthrene concentrations. Consumption of chargrilled food increased the 1-hydroxypyrene and hydroxyphenanthrene concentrations by 24% (95% CI: 11%, 37%) and 17% (95% CI: 8%, 26%) respectively. We did not find evidence of association for environmental tobacco smoke exposure or incense burning. It is concluded that both respiratory exposure and consumption of chargrilled food are considerable sources of PAH exposure in this population as reflected by concentrations of urinary biomarkers.
EVALuna2:9735